Oxidized LDL (oxLDL) activates the angiotensin II type 1 receptor by binding to the lectin‐like oxLDL receptor. Issue 8 (15th April 2015) - Yamamoto, Koichi; Kakino, Akemi; Takeshita, Hikari; Hayashi, Norihiro; Li, Lei; Nakano, Atsushi; Hanasaki‐Yamamoto, Hiroko; Fujita, Yoshiko; Imaizumi, Yuki; Toyama‐Yokoyama, Serina; Nakama, Chikako; Kawai, Tatsuo; et al.
Abstract : The angiotensin II type 1 receptor (AT1) is a 7‐transmembrane domain GPCR that when activated by its ligand angiotensin II, generates signaling events promoting vascular dysfunction and the development of cardiovascular disease. Here, we show that the single‐transmembrane oxidized LDL (oxLDL) receptor (LOX‐1) resides in proximity to AT1 on cell‐surface membranes and that binding of oxLDL to LOX‐1 can allosterically activate AT1‐dependent signaling events. oxLDL‐induced signaling events in human vascular endothelial cells were abolished by knockdown of AT1 and inhibited by AT1 blockade (ARB). oxLDL increased cytosolic G protein by 350% in Chinese hamster ovary (CHO) cells with genetically induced expression of AT1 and LOX‐1, whereas little increase was observed in CHO cells expressing only LOX‐1. Immunoprecipitation and in situ proximity ligation assay (PLA) assays in CHO cells revealed the presence of cell‐surface complexes involving LOX‐1 and AT1. Chimeric analysis showed that oxLDLinduced AT1 signaling events are mediated via interactions between the intracellular domain of LOX‐1 and AT1 that activate AT1. oxLDL induced impairment of endothelium‐dependent vascular relaxation of vascular ring from mouse thoracic aorta was abolished by ARB or genetic deletion of AT1. These findings reveal a novel pathway for AT1 activation and suggest a new mechanism whereby oxLDL may be promoting risk for cardiovascular disease.—Yamamoto, K., Kakino, A., Takeshita, H., Hayashi, N., Li, L., Nakano, A., Hanasaki‐Yamamoto, H., Fujita, Y., Imaizumi, Y., Toyama‐Yokoyama, S., Nakama, C., Kawai, T., Takeda, M., Hongyo, K., Oguro, R., Maekawa, Y., Itoh, N., Takami, Y., Onishi, M., Takeya, Y., Sugimoto, K., Kamide, K., Nakagami, H., Ohishi, M., Kurtz, T. W., Sawamura, T., Rakugi, H. Oxidized LDL (oxLDL) activates the angiotensin II type 1 receptor by binding to the lectin‐like oxLDL receptor. FASEB J. 29, 3342‐3356 (2015). www.fasebj.org